2020
DOI: 10.1007/s11845-020-02389-y
|View full text |Cite
|
Sign up to set email alerts
|

A national survey of attitudes to COVID-19 digital contact tracing in the Republic of Ireland

Abstract: Background Contact tracing remains a critical part of controlling COVID-19 spread. Many countries have developed novel software applications (Apps) in an effort to augment traditional contact tracing methods. Aim Conduct a national survey of the Irish population to examine barriers and levers to the use of a contact tracing App. Methods Adult participants were invited to respond via an online survey weblink sent via e-mail and messaging Apps and posted on our university website and on popular social media plat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
81
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 6 publications
(5 reference statements)
9
81
1
Order By: Relevance
“…With regard to open-ended text responses, 25% of participants in our study who did not download the COVIDSafe app were concerned about privacy. This is lower than the 31% in the smaller Australian study [ 10 ] and the 41% in the Irish study [ 11 ] who believed privacy was a problem. The differences in these percentages may be due to the free-text responses available in our survey, as the other studies used a list of options for participants’ responses.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…With regard to open-ended text responses, 25% of participants in our study who did not download the COVIDSafe app were concerned about privacy. This is lower than the 31% in the smaller Australian study [ 10 ] and the 41% in the Irish study [ 11 ] who believed privacy was a problem. The differences in these percentages may be due to the free-text responses available in our survey, as the other studies used a list of options for participants’ responses.…”
Section: Discussioncontrasting
confidence: 62%
“…The differences in these percentages may be due to the free-text responses available in our survey, as the other studies used a list of options for participants’ responses. Additionally, compared to the 11.1% of participants in our survey who did not download the app because they distrusted the government, there was more distrust in postpandemic government surveillance with Irish participants (33%) [ 11 ] and participants in the cross-country survey (42%) [ 12 ]. When considering communication strategies for improving contact tracing app downloads and use, better communication approaches are needed to put the public’s concerns about privacy and the government at ease.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Overall, international and French surveys (eg, [ 16 - 18 , 27 ]) have showed a higher acceptance of a contact tracing app than the real use we found in our study. Percentages of potential use of the app range from 38.4% [ 16 ] to 84% [ 21 ], which are substantially higher than the 4.7% (15/138) of respondents in our study who were using StopCovid. However, the lowest rates of acceptance for a contact tracing app were found mostly in France: 38.4% [ 16 ] and 44% [ 27 ].…”
Section: Discussionmentioning
confidence: 62%
“…Educational attainment, the presence of serious underlying health conditions, and the respondents’ stance on COVID-19 infection risks were also correlated with the predicted adoption rate. A national online survey on the Irish population (n=8088 responses) [ 21 ] showed that 84% of respondents would probably or definitely download the app. The most common reason for downloading the app was helping family members and friends (79%), and with a sense of responsibility to the wider community (78%).…”
Section: Introductionmentioning
confidence: 99%